Effect of population combinations on the reproductive success and germination of seeds of Bromus auleticus (Poaceae) - Gutiérrez, Hugo Francisco (2015)
Bromus auleticus is known for its qualities as forage but its domestication has limitations relating to seed production technology and farm-scale seed propagation. The effect of different combinations of population on the reproductive success and seed germination of a relict population of Argentina was studied. The tests used a population of Santa Fe (SF) as the recipient of pollen and three populations as donors (LP: La Pampa, ER: Entre Ríos and BA: Buenos Aires). Reproductive success was determined in plants from five pollination treatments: (i) (SFxSF), (ii) LP, (iii) ER, (iv) BA and (v) mixture of donor. Three temperature conditions were evaluated for germination: (i) 15°C, (ii) 28°C and (iii) alternating 15-28°C (12 h each). There were significant differences in reproductive success depending on the source of pollen. Seeds obtained from new genotypic combinations did not increase their weight in relation to the pollen donor. Germination behaviour was more affected by extrinsic factors (temperature) than by their genetic origin. However, under non-optimal germination conditions, seeds originating from new genotypic combinations showed a significant increase in germination percentage and germination rate. This work contributes additional knowledge to previous studies regarding the effect of pollen quality limitation on seed production and quality of B. auleticus. The results confirm the hypothesis that a mixture of genotypes from a diverse origin increases the quantity of flowers that become fruits and seed quality, which is of great importance to improved seed production and field establishment of B. auleticus.